The Islamic Social Finance in Poverty Alleviation: R Bibilioshiny Method Approach - Birjaman, Muhammad Iqbal; Ismail, Nurizal; Mahfudz, Shaifurrokhman (AL-IKTISAB: Journal of Islamic Economic Law, 2024)
The concept of Islamic social finance has gained significant attention in recent years as a tool for poverty alleviation. Islamic social finance refers to the use of Islamic financial instruments to address social and economic issues, including poverty, through zakat, infaq, shadaqah, and waqf. This research explores the application of Islamic social finance for poverty alleviation through the case study of the R Bibilioshiny program. Researchers conduct quantitative methods for data collection, primarily utilizing the Scopus database with the keyword "Islamic Social Finance on Poverty Alleviation". This research employs the R Bibilioshiny program application to process and visualize data obtained from the Scopus database. From the conceptual structure results in the thematic maps discussion, it is found that the most frequently appearing keywords closely related to the research are banking, poverty alleviation, and microfinance. This serves as a benchmark for influence, especially banking and microfinance as Islamic social finance in poverty alleviation efforts. The research finds that the R Bibilioshiny program has been successful in reducing poverty and improving the socio economic status of participants. The success of the R Bibilioshiny program highlights the potential of Islamic social finance as a tool for poverty alleviation. However, there are also challenges that need to be addressed, including the lack of awareness and understanding of Islamic social finance among the general public, and the need for more rigorous monitoring and evaluation of Islamic social finance programs to fully realize this potential, greater awareness and understanding of Islamic social finance is needed, as well as more rigorous monitoring and evaluation of Islamic social finance programs to ensure their effectiveness and sustainability.